PVD TiN and CrN Coated Austempered Ductile Iron: Analysis of Processing Parameters Influence on Coating Characteristics and Substrate Microstructure - Colombo, Diego Alejandro (2012)
This work studies the influence of the PVD processing parameters on the characteristics of TiN and CrN coatings deposited on ADI substrates, austempered at 360ºC, with different nodule counts and surface roughnesses. Coatings were applied by arc ion plating using an industrial reactor and different sets of parameters, with BIAS voltages, arc currents, chamber pressures and substrate temperatures varying from -100 to -250 V, 60 to 65 A, 0.7 to 2.8 Pa and 280 to 450ºC, respectively. The effect of the different depositions conditions on the substrates microstructure was also analyzed. The existing phases, preferred orientation, surface topography, film thickness, hardness and adhesion of each coating were determined. The retained austenite content and hardness of each substrate were computed before and after coating deposition.The results obtained indicate that the different deposition conditions and coating materials evaluated do not generate significant changes neither in the resulting topography nor in the coating adhesion, which can be related to indices between HF1 and HF2. Coating adhesion was not affected by different substrate roughnesses. The combined reduction of BIAS voltage, arc current and chamber pressure leads to a decrease of TiN growth rate and hardness, while high substrate temperatures promotes an increase in TiN and CrN growth rates. Substrate temperatures around 300ºC with deposition times of up to 240 min do not promote noticeable changes on the ausferritic microstructure,while temperatures of 400ºC and above translate into a clear microstructural deterioration, even for short deposition times.